ANALISIS PENURUNAN NILAI KEJUJURAN DAN AMANAH DALAM BISNIS ERA DIGITAL: URGENSI PENDIDIKAN ETIKA DIGITAL BERBASIS KETELADANAN RASULULLAH SAW - Srikandi Yudistira; Rustam; Pablo Sindo; Hartono (Tadbir: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to analyze the decline in honesty and trustworthiness in digital business practices and emphasize the relevance of the Prophet Muhammad's (PBUH) exemplary conduct as a foundation for business ethics. The research method used is a Systematic Literature Review (SLR) with a library research approach, through the collection and analysis of secondary data from journals, books, research reports, and trusted academic sources relevant to Islamic business ethics. The results of the study indicate that the digital era presents a shift in business orientation towards instant profits, thereby eroding the values of honesty and trustworthiness, which are reflected in advertising practices, review manipulation, exploitation and commodification of personal data, non-transparent algorithms, and unethical competition based on attention competition. Weak direct interaction, minimal digital literacy, and algorithmic systems that prioritize engagement. This study also found that digital trustworthiness has undergone a transformation in meaning from merely fulfilling promises to systemic responsibility, the use of technology, algorithm transparency, and business model integrity. The conclusion of the study emphasizes that strengthening ethics is not only moral-individual, but also systemic by using the Prophet Muhammad's (PBUH) exemplary conduct as a business operational framework that emphasizes proactive transparency, ethical consent, digital ethics education, and sharia-based regulations. The structural integration of sidq and amanah values ​​in digital is considered capable of creating businesses that are not only economically profitable, but also fair, sustainable, and blessed. Keywords: Amanah; Digital Business Ethics; Sidq